Education Guidelines and Basis Law-LDB: contributions to the inclusion of sexual and gender diversity in brazilian education (Research, Society and Development, 2022)
The objective of this writing is to discuss what the Lei de Diretrizes e Bases da Educação-LDB (Brazil, 1996) presents as a contribution on the topic of Sexual and Gender Diversity in education. It is part of the master’s Dissertation entitled Public Educational Policies and their actions for the Insertion of Sexual and Gender Diversity in Schools, which is being held at the Federal University of Amazonas-UFAM, on the Humaitá/AM campus. This is documental research and, therefore, of a qualitative nature, both in the theoretical assumptions presented in the first topic and in the analysis of the Lei de Diretrizes e Bases da Educação-LDB (Brazil, 1996). Topic discussions regarding the processes of implementation of educational policies and their mishaps. In the textual analysis, in the first topic there are discussions regarding the implementation processes of educational policies and their mishaps. When deepening the analysis, we discuss what the LDB (Brasil, 1996) must contribute on the inclusion of the Sexual and Gender Diversity Theme and how this happens. At this moment of investigation, it is possible to conclude that the theme should be discussed in the classroom in the format of a Transversal Theme and as a way of preventing all types of discrimination. This stance would guarantee or raise awareness that inequalities exclude differences and hide them through patriarchal culture.